Contact force catheter ablation for the treatment of persistent atrial fibrillation: Results from the PERSIST‐END study. (20th November 2022) - Lo, Monica; Nair, Devi; Mansour, Moussa; Calkins, Hugh; Reddy, Vivek Y.; Colley, B. Judson; Tanaka‐Esposito, Christine; Sundaram, Sri; DeLurgio, David B.; Sanders, Prashanthan; Khatib, Sammy; Bernard, Michael; et al.
Abstract: Introduction: Use of a novel magnetic sensor enabled optical contact force ablation catheter has been established to be safe and effective for treatment of symptomatic drug‐refractory paroxysmal atrial fibrillation (AF) but has yet to be demonstrated in the persistent AF (PersAF) population. Methods: PERSIST‐END was a multicenter, prospective, nonrandomized, investigational study designed to demonstrate the safety and effectiveness of TactiCath™ Ablation Catheter, Sensor Enabled™(SE) (TactiCath SE) for use in the treatment of subjects with documented PersAF refractory or intolerant to at least one Class I/III AAD. The ablation strategy included pulmonary vein isolation and additional targets at physician discretion. Follow‐up through 15‐months, including a 3‐month blanking period and 3‐month therapy consolidation period, was performed with cardiac event and Holter monitoring. Primary safety, primary effectiveness, clinical success, and quality of life (QOL) endpoints were analyzed. Results: Of 224 subjects enrolled at 21 investigational sites in the United States and Australia, 223 underwent ablation with the investigational catheter. The primary safety event rate was 3.1% (seven events in seven subjects). The Kaplan–Meier estimate of freedom from AF/atrial flutter/atrial tachycardia recurrence at 15‐months was 61.6% and clinical success at 15 months was 89.8%. Subject QOL significantly improved following ablation as assessed via AFEQT (31.6 point increase, p  < .0001) and EQ‐5D‐5L (10.7 point increase, p  < .0001) and was met with a 53% reduction in all cause cardiovascular healthcare utilization. Conclusion: The sensor‐enabled force‐sensing catheter is safe and effective for the treatment of drug refractory recurrent symptomatic PersAF, reducing arrhythmia recurrence while improving QOL and healthcare utilization. Abstract : Ablation with the sensor‐enabled force‐sensing catheter is safe and effective for the treatment of drug refractory recurrent symptomatic persistent atrial fibrillation, reducing arrhythmia recurrence while significantly improving quality of life and healthcare utilization.